Towards a Greater Professional Standing: Evolution of Pharmacy Practice and Education, 1920-2020 - Benjamin Y. Urick; Emily V. Meggs (MDPI AG, 2019)
The history of community pharmacy in America since the 1920s is one of slow progress towards greater professional standing through changes in pharmacy education and practice. The history of American community pharmacy in the modern era can be divided into four periods: 1920−1949 (Soda Fountain Era), 1950−1979 (Lick, Stick, Pour and More Era), 1980−2009 (Pharmaceutical Care Era), and 2010−present (Post-Pharmaceutical Care Era). As traditional compounding has waned, leaders within community pharmacy have sought to shift focus from product to patient. Increasing degree requirements and postgraduate training have enhanced pharmacists’ ability to provide patient care services not directly associated with medication dispensing. However, the realities of practice have often fallen short of ideal visions of patient-focused community pharmacy practice. Positive trends in the recognition of the impact of community pharmacists on healthcare value and the need for more optimal medication management suggest that opportunities for community pharmacists to provide patient care may expand through the 21st century.